APLIKASI TEKNOLOGI TRICHO-KOMPOS DAN PUPUK ORGANIK CAIR UNTUK MENINGKATKAN PRODUKSI SELADA ORGANIK - Purwanto, Purwanto; Tarjoko, Tarjoko; Haryanto, Agus (Jurnal Abdimas, 2018)
The main problem in organic lettuce production in Windujaya Village is low productivity as a result of the planting media relying only on nutrient intake from compost. The purpose of this activity is to introduce tricho-compost technology and liquid organic fertilizer to increase the productivity of organic lettuce plants. The method for carrying out this activity was through technology transfer through training and training carried out with demonstration plots. The results of the activity show that the cultivation of organic lettuce has been using simple technology so that the ability to meet market demand in terms of yield quality cannot be maximally fulfilled. It needs a breakthrough in marketing, not only fresh produce is sold, it needs an effort to be developed into agro tourism. Training in organic lettuce cultivation with biological agent technology and biofertilizers can significantly increase farmers' knowledge and skills in organic lettuce cultivation. The application of tricho-compost technology combined with POC can increase the production of lettuce plants by 20 percent with a profit of Rp. 150,000.00 per 100 polybags and farming efficiency of 1.88.